Ella Baker and the SNCC: Grassroots leadership and political activism in a nonhierarchical organization. - Charles, Joan E. (My University, 2007)
In SNCC, both men and women worked side by side in rural America. Some of SNCC's successes were due to the work of the large number of Black and White women in the organization. The study describes how SNCC promoted the development of leadership skills of the female activists and in doing so, the activists and local "Beloved Communities" were transformed.

This historical case study examined political activism and social movements as they relate to the life of Ella Baker and the Student Nonviolent Coordinating Committee (SNCC) in order to describe non-positional, grassroots leadership within a nonhierarchical organization that created social change in America. An examination of the life of Ella Baker and the organizational structure of the SNCC showed how women and men used non-traditional leadership roles to create, build, and maintain the momentum of a mass movement.

She did not seek credit for what she did, but she received gratification from witnessing people who enjoyed seeing others grow and emerge into leaders. She was a visionary leader. She created a new story, one not known to individuals before and achieved success in conveying this story effectively to others.

The study describes the leadership style of Ella Baker and the SNCC, thereby giving an alternative leadership style for schools and other organizations that are interested in restructuring their organizations to include full participation of all members. The study also describes the nature of community organizing in rural areas in America in the 1960s and clarified the process by which SNCC mobilized and transformed social structures. The study further describes the successes and constraints SNCC activists faced when they try to do so. Ella Baker and SNCC activists encouraged and supported emerging leadership among grassroots people.

Through the use of one semi-structured interview, archival, biographical, and scholarly materials, this study provides qualitative, historical data about group-centered leadership in a non-bureaucratic organization. Men and women will benefit from this study when they are ready to accept new ideas about leadership, full participation of organizational members, and change theory.
Keywords: Community leadership Case studies.; Baker, Ella, 1903-1986.; Political Science, General.; Gender Studies.; Student Nonviolent Coordinating Committee (U.S.); Women's Studies.; History, Black.; Social movements Administration Case studies.; Sociology, Organizational.; Biography.; Political participation Case studies.